Identification of Herbs and minerals in drugs, mentioned in the Treatment of Ear diseases(Sevi Noigal) in the Text of Pararajasekaram - Thayalini, T.; Thillany, P.V. (Unit of Siddha Medicine, University of Jaffna, 2017)
Many herbs, minerals, metals are used to prepare Siddha drugs. Diseases and treatments of Sevi Noigal (Ear Diseases) are mentioned in Pararajasekaram Siroroga Nidanam which is one of the Siddha Text in Jaffna District. The text Pararajasekaram, which was a work on medical sciences established in the medieval phase of Tamil literature during Singai Pararasasekaran's rule. Many internal and external Siddha drugs such as Chooranam (Powder), Thailam (Oil), Lehiyam (Confection), Kuzhambu (Mixture), Kuligai (Tablet) are mentioned in the Treatment of Sevi noigal. Each drug contains many herbal and mineral ingredients. The aim of the study is to identify the herbs and minerals in drugs mentioned in the treatment of Sevi Noigal in the text of Pararajasekaram. Drugs were taken from the literature which was used in the treatment of Ear diseases. First varieties of drugs were classified according to the application and preparation of drugs. After that ingredients of each drug were tabulated based on herbal and mineral, common herbs and minerals from each drug were identified from the tabulated sheet. Based on the table analysis, 19 Siddha drugs were identified for the treatment of Sevi Noigal. Among the 19 drugs, 58% (11) were Thailams, 16% (3) Chooranams, 16% (3) Lehiyams, 5% (1) and 5%(1) Kulambu. Among the 11 Thylams, 64% Neem oil, 36% Gingelly oil, 27% Castor oil, 18% Coconut oil and Pongamia pinnata oil used in the Preparation of Thailams. Out of 11 Thylams 55% (No 6) were used as Ear drops, 27% (No 3) applied on the head, 9% (1) consumed orally, and one as used for external application on skin of the ear oil. In these 19 Siddha drugs 214 ingredients were found. Out of 214 ingredients 86% (No 185) were herbs and 14% (No 29) are minerals. Highest percentage (over 58%) of herbs are Thirikaduku (Zingiber officinale, Piper longum and Piper nigrum) and rhizome of Acorus calamus in herbs and Cinnabar, Copper sulfate and Mercury in minerals were used to prepare the different forms of drugs. Common form of drug used in the treatment of Sevi noigal is Thailam (over 58%) with Neem oil as the base. Majority of the ingredients used in these thailams were previously reported o have anti-microbial activity. The text Pararajasekaram, mentions about thailams in the treatment of ear disease, out of which more than 50% of the thailams use Neem oil as the base and are fequently applied as eardrops. Based on the different studies, it is proved that Acorus calamus, Copper sulphate and Neem oil contains anti-microbial activity. Eventhough the antimicrobial effects of these ingredients wer unknown during the period of King Pararasasekaram, they had been included in the drug for the treatment of Sevi Noigal at the time.
Keywords: Herbs; Minerals; Drugs; Sevi noigal; Pararajasekharam